An Examination of the Relationship Between Height and Delinquency - Evans, Mary K. (Journal of developmental and life-course criminology, 2017)
Height has been shown to influence social development, which can affect life outcomes such as involvement in delinquent behaviors. Previous studies have linked height to aggression but have not examined other delinquent behaviors. The current study examines multiple ways that height can affect violence, property offending, and alcohol use.